1- When Haste Shakes the Scholar’s Pen: Some Scholarly Works on Dagbon after the Regicide of Yaa-Naa Yakubu Andani II, King of Dagbon, Ghana - Bolaji, M. H. A. (African Sociological Review, 2021)
Until the regicide of Yaa-Naa Yakubu Andani II, the Dagbon chieftaincy conflict – which has been intractable since the colonial era – was largely understudied. Nevertheless, the gruesome “murder” of the king provoked some scholarly interest in the Dagbon chieftaincy conflict. This article reviews significant scholarly works on the Dagbon chieftaincy conflict after the regicide. Also, it explores and interrogates the diverse perspectives which scholars have employed to explain the complexities of the conflict. Furthermore, it critiques some scholars’ uncritical acceptance that the rotational system of succession between the Abudu and Andani has been the tradition and presents the extent of its operation in Dagbon dynastic politics. Additionally, this article unearths some misrepresentations of historical facts and personalities and important dates. This article concludes that since historical truths play crucial roles in prosecuting intractablery to get the historical facts right in documenting them for posterity.